2010
DOI: 10.1901/jeab.2010.93-349
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reinforcement of Alternative Behavior Increases Resistance to Extinction: Clinical Demonstration, Animal Modeling, and Clinical Test of One Solution

Abstract: Basic research with pigeons on behavioral momentum suggests that differential reinforcement of alternative behavior (DRA) can increase the resistance of target behavior to change. This finding suggests that clinical applications of DRA may inadvertently increase the persistence of target behavior even as it decreases its frequency. We conducted three coordinated experiments to test whether DRA has persistence-strengthening effects on clinically significant target behavior and then tested the effectiveness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
258
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(296 citation statements)
references
References 28 publications
27
258
1
10
Order By: Relevance
“…Mace et al (2010) evaluated maintenance of treatment effects following DRA-based treatment. Findings from Mace et al (2010) indicated that DRA resulted in increased rates of reinforcement and, subsequently, increased persistence of other responses (i.e., problem behavior) that were in the same response class when extinction for the alternative response was placed on extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Mace et al (2010) evaluated maintenance of treatment effects following DRA-based treatment. Findings from Mace et al (2010) indicated that DRA resulted in increased rates of reinforcement and, subsequently, increased persistence of other responses (i.e., problem behavior) that were in the same response class when extinction for the alternative response was placed on extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Because alternative reinforcement increases the stimulus–reinforcer relationship of the context, it increases resistance to change despite its disruptive impact (see Nevin & Shahan, 2011, for discussion). For example, Mace et al (2010, Exp. 1) implemented alternative reinforcement in the treatment of problem behavior in three participants with developmental disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, if alternative reinforcers are presented within the same context as problem behavior, those added reinforcers, although intended to decrease problem behavior and replace it with socially desirable behavior, may actually increase the persistence of problem behavior when the intervention ends. Indeed, this perverse outcome has been obtained by Mace et al (2010) during interventions with children exhibiting problem behavior.…”
mentioning
confidence: 99%